Climate-change literacy of first year prospective physics teacher about long dry season phenomenon in Indonesia - Deta, Utama Alan; Arisanti, Aini; Laila, Luthfiyaul; Sasmi, Rinda Rahmanisa; Lestari, Nurita Apridiana; Saregar, Antomi; Mubarok, Husni (Journal of Environment and Sustainability Education, 2023)
Indonesia has characteristics of increasing temperatures that have yet to be widely known. Sudden temperature changes have brought many losses to Indonesians. The study was intended to analyze the level of scientific literacy on the climate-change material for prospective physics teachers in Indonesia. The study employs a qualitative methodology. The study also utilized descriptive analysis techniques by administering surveys to gather participant data. This study uses descriptive analysis techniques through the administration of surveys to collect data from participants. Increased emissions of greenhouse gases are a contributing factor to changes in temperature and climate. The escalation of greenhouse gas emissions in Indonesia leads to climate change as these gases envelop the Earth and trap the sun's heat, intensifying the greenhouse effect. The outcome entails elevated mean temperatures, alterations in precipitation patterns, and occurrences of severe weather events such as floods and droughts. Evaluating climate or temperature changes necessitates education. Education imparts knowledge about the significance of safeguarding the planet to maintain its well-being. Education plays a crucial role in addressing the challenge of climate change, particularly the Sustainable Development Goals (SDGs).